Maintaining the quality of postharvest broccoli by inhibiting ethylene accumulation using diacetyl - Li, Xiaotong; Meng, Zan; Malik, Aman Ullah; Zhang, Song; Wang, Qingguo (Frontiers in Nutrition, 2022)
Broccoli (Brassica oleracea L. var. Italic) is rich in nutrition. However, it is susceptible to yellowing after harvest, leading to nutritional and economic losses. In this study, diacetyl, a natural food additive compound, was selected to inhibit the yellowing of broccoli florets and maintain the nutrient quality during storage time. It was found that 20 µL L-1 diacetyl treatment for 12 h could significantly delay the yellowing and decrease the weight loss and lignin content of broccoli florets. Meanwhile, diacetyl could maintain higher contents of chlorophyll, vitamin C and flavonoids and suppress the transcript levels of chlorophyll degradation–related genes in broccoli florets. Moreover, accumulations of reactive oxygen species (ROS) were inhibited by diacetyl treatment. Under diacetyl treatment, the generation of ethylene was prevented by inhibiting the activities and related-gene expressions of 1-aminocyclopropane-1-carboxylic acid (ACC) synthase and ACC oxidase. Based on our findings, exogenous diacetyl could be employed as a novel bioactive molecule for retarding the yellowing and maintaining the quality of postharvest broccoli.